Properties and bending behavior of Nickel coated Mild steel sheet during air bending (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Springback refers to the elastic recovery which subject to a geometrical change when the metal undergoes deformation during the forming process. The experimental investigation of this paper is focused to analyze the behavior of spring back of nickel coated mild steel (NCMS) sheets during the air bending process. The hardeness and surface roughness was measured after coating. Experimental investigation have been conducted to resolve the influence of control parameters such as Orientations (Î¸), Width of the sheet (Ws), Punch travel (Tp), Holding time (Ht) and Punch Velocity (v) on spring back behavior. As a results, the incraese in Orientations, Width of the sheet, Punch travel andd Punch Velocity incraese the springback angle.